Exergy, Emission, and Operational Cost Analysis of Cofiring Coal-Fired Power Plant Systems - Arya Adi Saputra (Green Publisher Indonesia, 2025)
Indonesia's electricity sector remains heavily dependent on coal-fired steam power plants (PLTU), which account for more than 50% of the national energy mix. This study aims to evaluate the impact of biomass cofiring implementation on the thermodynamic, environmental, and economic performance of PLTU Banten 2 Labuan Unit 1, which has a capacity of 300 MW. The methodology involves thermodynamic simulation using Cycle-Tempo software to calculate energy efficiency and exergy, as well as the cost of exergy destruction as part of an exergoeconomic analysis. The results show that the cofiring scenario of 95% coal and 5% biomass is the most optimal configuration. This scenario yields an exergy efficiency of 37.55%, with a reduction in exergy destruction of 7,119 kW compared to 100% coal. Economically, it provides fuel cost savings of 3.2% and a reduction in the cost of exergy destruction of Rp1,623,600 per hour. Environmentally, it reduces CO₂ emissions by 6.25 tons per hour, demonstrating a tangible contribution to emissions reduction in the energy sector. This study concludes that biomass cofiring technology, especially at a 95:5 ratio, offers a viable energy transition solution that can be gradually adopted by existing coal-fired power plants in Indonesia. The results are expected to serve as a technical and strategic reference for developing low-carbon energy policies and optimizing the operation of biomass-cofiring-based power plants.